Answer
$\color{blue}{\dfrac{p^4}{5}}$
Work Step by Step
RECALL:
(1) $a^{-m} = \dfrac{1}{a^m}$
(2) $\dfrac{a^m}{a^n} = a^{m-n}$
(3) $\left(\dfrac{a}{b}\right)^m=\dfrac{a^m}{b^m}$
(4) $(ab)^m = a^mb^m$
(5) $(a^m)^n=a^{mn}$
(6) $a^m \cdot a^n = a^{m+n}$
(7) $a^0=1, a\ne0$
Use rule (7) above to obtain:
$=\dfrac{1}{5p^{-4}}$
Use rule (1) above to obtain:
$=\dfrac{1}{5\cdot \frac{1}{p^4}}
\\=\dfrac{1}{\frac{5}{p^4}}$
Use the rule $a \div \dfrac{b}{c} = a \cdot \dfrac{c}{b}$ to obtain:
$=1 \cdot \dfrac{p^4}{5}
\\=\color{blue}{\dfrac{p^4}{5}}$